2007
DOI: 10.1093/jnci/djk095
|View full text |Cite
|
Sign up to set email alerts
|

MLH1 -93G>A Promoter Polymorphism and the Risk of Microsatellite-Unstable Colorectal Cancer

Abstract: In two patient populations, the MLH1 -93G>A polymorphism was associated with an increased risk of MSI-H colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
114
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(131 citation statements)
references
References 53 publications
9
114
2
6
Order By: Relevance
“…9 These observations suggest that the MLH1 293G>A polymorphism might affect risk of CRC. Consistent with this hypothesis, the MLH1 293A variant has been associated with an increased risk of developing hyperplastic colonic polyps in smokers, 10 CRC in persons with a family history of this disease 11 and microsatellite unstable CRC. 11 …”
mentioning
confidence: 63%
See 1 more Smart Citation
“…9 These observations suggest that the MLH1 293G>A polymorphism might affect risk of CRC. Consistent with this hypothesis, the MLH1 293A variant has been associated with an increased risk of developing hyperplastic colonic polyps in smokers, 10 CRC in persons with a family history of this disease 11 and microsatellite unstable CRC. 11 …”
mentioning
confidence: 63%
“…The MLH1 293A variant has previously been associated with an increased risk of developing hyperplastic colonic polyps in smokers, 10 CRC in persons with a family history of this disease, 11 and microsatellite-unstable CRC. 11 Taken together with our findings, these data suggest that the MLH1 293A variant defines a low penetrance risk allele for MMR-deficient CRC. Moreover, our observations extend this model by suggesting an association between the 293A variant and CRC with loss of MLH1 protein specifically.…”
Section: Discussionmentioning
confidence: 99%
“…5,33,38-42 We found no evidence for an association between the MLH1 promoter germline SNP c.-93G4A genotype and an increased risk of MLH1 methylation or microsatellite instability in a case-control study of this cohort, arguing against a cis-acting role for this SNP in conferring susceptibility to methylation. In previous studies in which a positive association was found between the G4A genotype and microsatellite instability, either familial cases were retained in the cohort or the study group comprised early-onset cases, [8][9][10][11] suggesting that the genotype may be linked to founder mutations that give rise to familial or early-onset cancer phenotypes in these populations. Although in one study of a large colorectal cancer cohort, the c.-93G4A genotype was shown to be associated with MLH1 methylation, the BRAF V600E mutation as well as CIMP þ among sporadic microsatellite unstable cancers, nevertheless a stronger association between the G4A genotype was demonstrated among the microsatellite unstable cases with a positive family history.…”
Section: Discussionmentioning
confidence: 99%
“…6 The c.-93G4A SNP (rs1800734) within the MLH1 promoter has been associated with an increased risk of microsatellite instability or MLH1 methylation in some colorectal and endometrial cancer populations, but not in others. [7][8][9][10] However, these associations have been disputed on the basis that linkage disequilibrium with pathogenic mutations could not be ruled out in populations with a high incidence of familial cancer. 11 Recently, promoter reporter assays showed that the A allele of this SNP conferred reduced transcriptional activity compared with the G allele, consistent with the notion that this allele might predispose to promoter methylation.…”
mentioning
confidence: 99%
“…There are 20 case-control studies concerning -93G>A polymorphism (Ito et al, 1999;Deng et al, 2003;Park et al, 2004;Chen et al, 2005;Lee et al, 2005;Beiner et al, 2006;Song et al, 2006;Raptis et al, 2007;An et al, 2008;Harley et al, 2008;Koessler et al, 2008;Scott et al, 2008;Tulupova et al, 2008;Campbell et al, 2009;Shi et al, 2010;Shih et al, 2010;van Roon et al, 2010;Lacey et al, 2011;Lo et al, 2011;Whiffin et al, 2011) and 18 studies for I219V (Mathonnet et al, 2003;Listgarten et al, 2004;Lee et al, 2005;Mei et al, 2006;Song et al, 2006;Raptis et al, 2007;An et al, 2008;Capella et al, 2008;Smith et al, 2008;Campbell et al, 2009;Conde et al, 2009;Joshi et al, 2009;Nejda et al, 2009;Tanaka et al, 2009;Langeberg et al, 2010;Picelli et al, 2010 polymorphisms are summarized in Table 1. Most studies indicated that the genotypes distribution in the controls was consistent with Hardy-Weinberg equilibrium except for six studies for -93G>A (Park et al, 2004;Beiner et al, 2006;An...…”
Section: Characteristics Of Studiesmentioning
confidence: 99%